Spatial heterogeneity determines the gastrointestinal microbiome signatures and ecological processes that govern bacterial community assembly in sheep - Yukun Zhang; Jiangbo Cheng; Changchun Lin; Fadi Li; Xiaoxue Zhang; Chong Li; Deyin Zhang; Xiaobin Yang; Dan Xu; Yuan Zhao; Liming Zhao; Xiaolong Li; et al. (Microbiology Spectrum)
ABSTRACT Sheep are one of the globally significant livestock, providing meat, dairy products, and wool for human life, playing an indispensable role in human civilization. Despite significant advancements in microbiome research in recent years, most studies have focused solely on the rumen, lacking a comprehensive study covering the microbiome of different gastrointestinal tract (GIT) regions in sheep. In this study, we collected 338 samples from 10 different regions of the sheep GIT and systematically investigated their microbiome signatures, including community structure, enterotypes, interactions among taxa, and microbial community assembly. Our results showed that the bacterial diversity of sheep GIT exhibited a U-shaped pattern along the GIT, with the lowest diversity in the jejunum. The bacterial community composition and enterotype varied along the GIT, mainly divided into three distinct groups (four-chambered stomach, small intestine, and large intestine). The rumen had the highest total number of bacterial taxa, unique taxa, and unique functions, while the enterotypes were the same in the three regions of the large intestine. The bacterial co-occurrence networks differed greatly between different GIT regions, with more positive correlations than negative ones. Furthermore, we found that the assembly processes of bacterial communities in the four-chambered stomach and small intestine were mainly stochastic, while those in the large intestine were mainly shaped by deterministic processes, with a higher ecological niche width than other GIT regions. Our results reveal the spatial pattern of bacterial communities in the sheep GIT and the intrinsic mechanisms of bacterial community assembly, laying the foundation for microbial interventions to improve sheep productivity and sustainable farming.IMPORTANCESheep's gastrointestinal tract harbors a diverse microbial community crucial for immune system balance, nutrient digestion, and overall health. We explored the microbial community composition, community types (enterotypes), bacterial interactions, and ecological processes in 10 gastrointestinal regions of 36 six-month-old Hu sheep raised under same diets and environmental conditions. Our findings revealed a unique U-shaped pattern of bacterial diversity from the rumen to the rectum, with the lowest diversity in the jejunum. The composition and enterotypes of bacterial communities varied spatially along the gastrointestinal tract, primarily categorized into three distinct groups. The rumen exhibited the highest abundance of bacterial taxa, unique taxa, and unique functions, while the enterotypes in the three regions of the large intestine were consistent. We explored the assembly processes of bacterial communities, elucidating how they find their ecological niches based on their characteristics and environmental demands. The assembly processes in the four-chambered stomach and small intestine resembled random selection, where bacterial positioning depended on luck and chance, while in the large intestine, it appeared more deterministic, with specific bacteria likely selected based on their unique skills and environmental requirements. This study enhances our understanding of microbial coexistence and interactions in complex ecosystems, with implications for improving animal productivity, disease treatment, and the development of novel microbial formulations.